Answer Set Programming for Bus Route Finding: A Case Study in Bangkok, Thailand - Racharak, Teeradaj; Mon, Su Yee; Chawuthai, Rathachai (My University, 2026)
Finding user-satisfied bus routes subject to the minimal travel time and the number of route transfers is a challenging problem in transportation networks. In our context, bus routes and bus stations form a directed graph. Thus, a solution to finding the user-satisfied bus routes is a route path between two given stations satisfying a collection of different user's constraints. While this problem could be related to existing research, such as, the study of graph traversal and path finding algorithms. We show that our problem is more suited to formalizing the navigation system in terms of several related answer set programs (ASPs), where each module has its own isolated function, rather than treating like common graph traversal problems such as the well-known Dijkstra's algorithm, which only provides a statically single solution with lowest cost. Our empirical study with a real-world bus network data confirms that our ASPs encoding works in producing a wide range of high-quality solutions, offering more flexibilities between different optimization criteria, compared with the fixed Dijkstra's optimization results. The findings show promise for extending to richer transit representations and optimization objectives beyond the two considered here.
Keywords: Automated Planning; Graph Traversal; Knowledge Representation; Logic Programming; Route Optimization